SINGLE NUCLEOTIDE POLYMORPHISMS OF TRANSFORMING GROWTH FACTOR-Î’1 GENE AS POTENTIAL ASTHMA SUSCEPTIBLE VARIANTS IN PUNJABI POPULATION OF PAKISTAN - Akram, Muhammad; Sabar, Muhammad Farooq; Bano, Iqbal; Ghani, Muhammad Usman; Shahid, Mariam (Journal of Ayub Medical College Abbottabad, 2022)
Background: Candidate gene approach based on case-control model is a valuable strategy to determined disease related genetic variants. Two single nucleotide polymorphisms rs1800469 and rs2241715 in TGF-Î²1gene have been reported to affect the asthmatic status in different populations. The main focus of this research was to find any relationship between these SNPs and asthma in Pakistani population. Methods Using case-control model, a total of 108 individuals including 52 asthma patients and 56 healthy controls were screened to find asthma susceptibility of variants rs1800469 and rs2241715. These SNPs were genotyped using SNaPshot minisequencing assay followed by capillary electrophoresis using ABI 3130xl genetic analyzer platform. The statistical analysis of genetic data was performed by using SPSS 21, SHEsis online platform and SNPStats online web software. Results: No association with asthma was seen in allelic model for both SNPs but genotypes analyzed under codominant, dominant, over dominant and recessive models of inheritance revealed that SNP rs2241715 is strongly associated with asthma under genotypic model. Conclusion: rs2241715 was found to be a genetic risk factor for asthma in Pakistani population.